2014
DOI: 10.1373/clinchem.2014.224832
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of Pheochromocytoma and Paraganglioma

Abstract: BACKGROUND: Pheochromocytomas and paragangliomas (PPGLs) are potentially lethal yet usually surgically curable causes of endocrine hypertension; therefore, once clinical suspicion is aroused it is imperative that clinicians choose the most appropriate laboratory tests to identify the tumors. CONTENT:Compelling evidence now indicates that initial screening for PPGLs should include measurements of plasma free metanephrines or urine fractionated metanephrines. LC-MS/MS offers numerous advantages over other analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 77 publications
0
77
0
6
Order By: Relevance
“…Phaeochromocytomas and most thoraco-abdomino-pelvic paragangliomas are of sympathetic origin. In most PPGL, chromaffin cells produce one or more catecholamines that are metabolised into MN or 3MT (1,3). Most parasympathetic paragangliomas are found in the head or neck and do not usually produce catecholamines.…”
Section: Ppglsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phaeochromocytomas and most thoraco-abdomino-pelvic paragangliomas are of sympathetic origin. In most PPGL, chromaffin cells produce one or more catecholamines that are metabolised into MN or 3MT (1,3). Most parasympathetic paragangliomas are found in the head or neck and do not usually produce catecholamines.…”
Section: Ppglsmentioning
confidence: 99%
“…Descriptions of several series have shown that malignant primary tumours are more frequently extraadrenal (paraganglioma rather than phaeochromocytoma) than apparently benign primary tumours (review in (8) and Section 4). High levels of 3MT are found in patients with malignant PPGL (3,10). Primary malignant tumours and malignant recurrences are frequent in SDHB mutation carriers and may also occur in FH and MDH2 mutation carriers (1,4,5,6,7,8,9 …”
Section: )mentioning
confidence: 99%
“…У пациентов с биохимически "молчащими" опухолями определение уровня хромогранина А как универсального биомаркера нейроэндо-кринных опухолей является важным вспомо-гательным тестом [58].…”
Section: биохимическая диагностикаunclassified
“…Estima-se uma taxa de recorrência de 1/100 casos (sendo mais de 40% destas recorrências correpondentes a casos de malignidade) [7,52]. Sendo assim, recomenda-se em todos os pacientes uma monitorização laboratorial anual (metanefrinas plasmáticas ou urinárias e cromogranina A) e com exames de imagem (ponderar a realização de ressonância magnética tóraco-abdomino-pélvica a cada um ou dois anos) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: /10unclassified
“…Os tumores secretores de catecolaminas têm origem em células cromafins da medula da suprarrenal no caso dos feocromocitomas (estes são tumores total ou parcialmente encapsulados, muito vascularizados, sendo que 85 a 95% são tumores únicos, com diâmetro inferior a 5 cm); e dos gânglios simpáticos extra-adrenais no caso dos paragangliomas (cabeça e pescoço em 70%, região abdomino-pélvica em 20% e torácica em 10%) [7,13,[15][16][17][18]. Até 47% dos feocromocitomas são malignos, e como não há características histológicas, bioquímicas ou de microscopia eletrônica para a malignidade, esta é definida exclusivamente pela presença de metástases (sobretudo nos gânglios linfáticos, fígado, pulmão e osso) [7,15,17,[19][20][21][22].…”
Section: Introductionunclassified